SmartPresence: Aplikasi Absensi Sekolah Berbasis Android - Hardi Saputra; Taslim Taslim; Muhammad Nurramadhani; Sukma Riski Ananda (Progressive Information, Security, Computer, and Embedded System, 2026)
Student attendance is an important indicator in supporting the effectiveness of the learning process and school administrative management. However, conventional attendance systems that are still conducted manually often lead to various problems, including recording errors, delays in data recapitulation, and low efficiency in attendance monitoring. This study aims to design and develop SmartPresence, an Android-based school attendance application that supports digital, effective, and real-time attendance management. The system was developed using the Waterfall model, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The application was built using Java programming language in Android Studio, with Firebase Realtime Database as the data storage platform and Quick Response Code (QR Code) technology as the attendance validation mechanism. The results show that SmartPresence successfully integrates user authentication, monitoring dashboard, QR Code-based attendance, attendance history, and digital attendance reports into a single integrated platform. Based on Black Box Testing involving 19 testing scenarios, all system functions operated successfully according to user requirements, achieving a 100% success rate. The findings indicate that SmartPresence is capable of improving the efficiency of attendance management while supporting the digital transformation of school administration through fast, accurate, and easily accessible attendance information. Keywords: Digital Attendance, Android Application, Student Attendance, School Management, SmartPresence